KARAKTERISTIK ATC Kappaphycus alvarezii PADA PERLAKUAN UMUR PANEN DAN SUHU EKSTRAKSI BERBEDA - Mahbub L Furada; Widodo F Ma’ruf; Eko N Dewi (Jurnal Perikanan Universitas Gadjah Mada, 2012)
One of the ATC quality is influenced by the length time of harvesting and temperature of extraction.The aimof the research was to determine the influenced of different time of harvesting K.alvarezii and the degree temperatureextraction process to the quality of the ATC product (yield, gel strength and viscosity). The material used wastaken from the Bandengan coastal area, Jepara. The treatments used was the difference temperature of extractionprocess which are 70oC and 80oC and the difference of harvesting time 35, 40, and 45 days. K.alvarezii extracted using6% KOH solution for 4 hours, dried and then is milled. The yield test showed that the used extraction temperatureof 80oC produces a higher yield than the temperature of 70oC, the percentage yield of ATC powder was increasein along with harvesting time of K.alvarezii. The gel strength test showed that the use of extraction temperature of70oC produces a higher gel strength and viscosity than the temperature of 80oC, the highest gel strength obtainedat 40 days harvesting time of seaweed.One of the ATC quality is infl uenced by the length time of harvesting and temperature of extraction.The aimof the research was to determine the infl uenced of different time of harvesting K.alvarezii and the degree temperatureextraction process to the quality of the ATC product (rendemen, gel strength and viscosity). The material used wastaken from the Bandengan coastal area, Jepara. The treatments used was the difference temperature of extractionprocess which are 70oC and 80oC and the difference of harvesting time 35, 40, and 45 days. K.alvarezii extracted using6% KOH solution for 4 hours, dried and then is milled. The yield test showed that the used extraction temperatureof 80oC produces a higher yield than the temperature of 70oC, the percentage yield of ATC powder was increasein along with harvesting time of K.alvarezii. The gel strength test showed that the use of extraction temperature of70oC produces a higher gel strength and viscosity than the temperature of 80oC, the highest gel strength obtainedat 40 days harvesting time of seaweed.